KARAKTERISTIK TUMOR PAYUDARA PADA WANITA UMUR 35 - 65 TAHUN DI RSUD DR. H. ABDUL MOELOEK BANDAR LAMPUNG TAHUN 2018 - Rima Nurbaiti; Festy Ladyani Mustofa; Ratna Purwaningrum; Nengah Budiarta (Medula, 2023)
Cancer has a unique characteristic, which consists of malignant cells that can spread to other parts of the body. This spread is called metastasis and can occur through blood vessels or lymph vessels.This research is observational descriptive by using a cross sectional method approach using purposive sampling technique with a total of 105 samples. Data collection began in November 2019. This research was conducted at RSUD Dr. H. Abdul Moeloek Bandar Lampung. Statistical data chi-square test using SPSS 25. The research respondents obtained totaled 105 samples obtained 88 subjects. Respondents with > 40 years are as many as 66 people (75.0%), family history of breast tumors as many as 4 people (4.5%). radiation history as many as 3 people (3.4%). history of using hormonal family planning as many as 26 people (29, 5%). tumor size >5cm as many as 52 people (59.1%). Types of malignant tumors as many as 57 people (64.8%). The majority of respondents were > 40 years old, had a family history of breast tumors, and a history of radiation, a history of using hormonal contraception.